2009
DOI: 10.1126/science.1176105
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of Molecular Orbital Densities from Photoemission Data

Abstract: Photoemission spectroscopy is commonly applied to study the band structure of solids by measuring the kinetic energy versus angular distribution of the photoemitted electrons. Here, we apply this experimental technique to characterize discrete orbitals of large pi-conjugated molecules. By measuring the photoemission intensity from a constant initial-state energy over a hemispherical region, we generate reciprocal space maps of the emitting orbital density. We demonstrate that the real-space electron distributi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

22
414
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 318 publications
(437 citation statements)
references
References 28 publications
22
414
0
1
Order By: Relevance
“…A similar approach was successfully applied to analyze angular resolved photoemission (ARPES) spectra of oligomeric organic molecules [13]. In our scheme, selected φ i (r) expanded on a real space grid is projected to momentum space either using discrete 3-D Fast Fourier Transform (FFT) or by the projection onto a set of plane waves e ik .r :φ…”
Section: Knownmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar approach was successfully applied to analyze angular resolved photoemission (ARPES) spectra of oligomeric organic molecules [13]. In our scheme, selected φ i (r) expanded on a real space grid is projected to momentum space either using discrete 3-D Fast Fourier Transform (FFT) or by the projection onto a set of plane waves e ik .r :φ…”
Section: Knownmentioning
confidence: 99%
“…To the best of our knowledge, only a few attempts [12][13][14][15] have been made to perform the projection of states of finite systems from real to reciprocal space and vice versa so far. Therefore, a robust method which allows the band structure mapping from fully relaxed density functional theory (DFT) calculations of realistic Si NCs is required.…”
Section: Introductionmentioning
confidence: 99%
“…The theoretical approach of considering single molecules is justified by the fact that, as seen by XPS and UPS, the metal/molecule interaction is weak and the molecular orbitals do not change their character upon adsorption [37][38][39] as we will discuss later in more detail. The results are presented in Figure 3 The Voigt profile is chosen in order to take into account both the finite core-hole lifetime (which has a Lorentzian profile) and the broadening due to the finite experimental resolution as well as various inhomogeneities, e.g., molecular packing and local morphology [24] (Gaussian profile).…”
mentioning
confidence: 99%
“…A small discrepancy appears at large angles between photoelectron momentum vector q and in in accordance with Refs. [29][30][31].…”
Section: Appendix A: Derivation Of the Time-and Angle-resolved Photoementioning
confidence: 99%
“…Although the plane-wave approximation can yield incorrect results in the case of some molecules or experimental conditions [28], it has been shown that this approximation is appropriate for the calculation of angle-resolved photoemission spectra from π orbitals of planar molecules consisting of light atoms at small angles between in and q [29][30][31]. Still, our main motivation to apply the plane-wave approximation is to provide an example of an analysis of time-and angleresolved photoelectron spectra within the most straightforward approximation to the photoelectron wave function that leads to the following result:…”
mentioning
confidence: 99%